Development of criteria for cognitive dysfunction in post-COVID syndrome: the IC-CoDi-COVID approach. (January 2023) - Matias-Guiu, Jordi A; Herrera, Elena; González-Nosti, María; Krishnan, Kamini; Delgado-Alonso, Cristina; Díez-Cirarda, María; Yus, Miguel; Martínez-Petit, Álvaro; Pagán, Josué; Matías-Guiu, Jorge; Ayala, José Luis; Busch, Robyn; et al.
Highlights: Cognitive complaints are one of the most frequent symptoms in post-COVID syndrome. There is no consensus about the definition of cognitive impairment in this entity. Two clusters according to the severity of cognitive dysfunction were found. We propose a harmonization of the criteria for the definition of cognitive impairment. Abstract: Background: We aimed to develop objective criteria for cognitive dysfunction associated with the post-COVID syndrome. Methods: Four hundred and four patients with post-COVID syndrome from two centers were evaluated with comprehensive neuropsychological batteries. The International Classification for Cognitive Disorders in Epilepsy (IC-CoDE) framework was adapted and implemented. A healthy control group of 145 participants and a complementary data-driven approach based on unsupervised machine-learning clustering algorithms were also used to evaluate the optimal classification and cutoff points. Results: According to the developed criteria, 41.2% and 17.3% of the sample were classified as having at least one cognitive domain impaired using -1 and -1.5 standard deviations as cutoff points. Attention/processing speed was the most frequently impaired domain. There were no differences in base rates of cognitive impairment between the two centers. Clustering analysis revealed two clusters, although with an important overlap (silhouette index 0.18-0.19). Cognitive impairment was associated with younger age and lower education levels, but not hospitalization. Conclusions: We propose a harmonization of the criteria to define and classify cognitive impairment in the post-COVID syndrome. These criteria may be extrapolated to other neuropsychological batteries and settings, contributing to the diagnosis of cognitive deficits after COVID-19 and facilitating multicenter studies to guide biomarker investigation and therapies.